Photocatalysis - Bignozzi, Carlo Alberto; Alexander, B. D.; SpringerLink (Online service). (Berlin New York Springer, 2011)
Metal Oxide Photoanodes for Water Splitting, by J. Augustynski, B. D. Alexander and R. Solarska; Hydrogen Production with Nanostructured and Sensitized Metal Oxides , by Stefano Caramori, Vito Cristino, Laura Meda, Roberto Argazzi and Carlo Alberto Bignozzi; Surface Nanostructures in Photocatalysts for Visible-Light-Driven Water Splitting, by Kazuhiko Maeda and Kazunari Domen; Artificial Photosynthesis Challenges: Water Oxidation at Nanostructured Interfaces, by Mauro Carraro, Andrea Sartorel, Francesca Maria Toma, Fausto Puntoriero, Franco Scandola, Sebastiano Campagna, Maurizio Prato and Marcella Bonchio; Photocatalytic Reduction of CO2: From Molecules to Semiconductors, by Tatsuto Yui, Yusuke Tamaki, Keita Sekizawa and Osamu Ishitani; Design of Heterogeneous Photocatalysts Based on Metal Oxides to Control the Selectivity of Chemical Reactions, by Andrea Maldotti and Alessandra Molinari.
Metal Oxide Photoanodes for Water Splitting, by J. Augustynski, B. D. Alexander and R. Solarska -- Hydrogen Production with Nanostructured and Sensitized Metal Oxides , by Stefano Caramori, Vito Cristino, Laura Meda, Roberto Argazzi and Carlo Alberto Bignozzi -- Surface Nanostructures in Photocatalysts for Visible-Light-Driven Water Splitting, by Kazuhiko Maeda and Kazunari Domen -- Artificial Photosynthesis Challenges: Water Oxidation at Nanostructured Interfaces, by Mauro Carraro, Andrea Sartorel, Francesca Maria Toma, Fausto Puntoriero, Franco Scandola, Sebastiano Campagna, Maurizio Prato and Marcella Bonchio -- Photocatalytic Reduction of CO2: From Molecules to Semiconductors, by Tatsuto Yui, Yusuke Tamaki, Keita Sekizawa and Osamu Ishitani -- Design of Heterogeneous Photocatalysts Based on Metal Oxides to Control the Selectivity of Chemical Reactions, by Andrea Maldotti and Alessandra Molinari.
Electronic reproduction.
Keywords: Photocatalysis; Organic Chemistry; Physical Chemistry; Renewable and Green Energy; Electronic books